Penyelesaian Permohonan Fiktif Positif untuk Mendapatkan Keputusan di Pengadilan Tata Usaha Negara - Ni Komang Ayu Arniti; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2019)
The Enactment of Law (No.) 30 of 2014 on Government Administration raises a new paradigm related to silence or neglect of agencies or officials of State administration where if within the specified time limit does make decisions or actions, then the application is deemed granted law and to obtain an acceptance decision the applicant must submit an application to the Administrative Court. As for the formulation of the problem in this case 1) What is the mechanism of a positive fictitious application in the event that a state administrative body or official does not issue a decision on a request submitted by its citizens? 2) What is the Judge's Consideration in completing the application at the Denpasar State Administrative Court? The method in this study is a type of normative juridical research that is by conducting a legal approach and case approach. The sources of legal material that will be used are sourced from research, the literature in the form of primary and secondary legal materials. The technique of collecting legal materials by means of inventory is then carried out identification and classification of legal materials. Legal materials are analyzed with systematic interpretations by applying inductive logic, which is trying to find legal rules, then do discussions to get answers to the problems under study. Regarding the mechanism for resolving positive fictitious applications set out in Supreme Court Regulation (No.) 8 of 2017. A positive fictitious application is an application for the issuance of a decision and or a new official governmental action, not a cancellation of existing decisions, because the formality of the application is not fulfilled as a fictitious positive application, then at such discretion the Assembly of Judges is of the opinion that the petition of the Petitioner is unacceptable.